2021
DOI: 10.2147/idr.s298274
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tigecycline Combined with Azithromycin Against Biofilms of Multidrug-Resistant Stenotrophomonas maltophilia Isolates from a Patient in China

Abstract: Purpose Our aim was to investigate in vitro biofilm formation by S. maltophilia and the effects of antibacterial agents used to prevent biofilm formation. Methods Two trimethoprim/sulfamethoxazole-resistant S. maltophilia strains were isolated from the pleural effusion of a patient with cancer. The minimum inhibitory concentrations (MICs) of amikacin, azithromycin, cefoperazone/sulbactam, and tigecycline were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…We validated the synergistic interaction of azithromycin in combination with all three PCs. This was in agreement with several studies reporting the bactericidal and antibiofilm action of azithromycin combined with tigecycline (59), and colistin (60,61) against different Gram-negative bacilli. The interaction with fosfomycin is novel.…”
Section: Discussionsupporting
confidence: 93%
“…We validated the synergistic interaction of azithromycin in combination with all three PCs. This was in agreement with several studies reporting the bactericidal and antibiofilm action of azithromycin combined with tigecycline (59), and colistin (60,61) against different Gram-negative bacilli. The interaction with fosfomycin is novel.…”
Section: Discussionsupporting
confidence: 93%
“…This addition further improves the antibacterial effect of tigecycline against pan drugresistant pathogens. 10,11 However, tigecycline is widely distributed in tissues, resulting in relatively low blood drug concentrations. Consequently, tigecycline benefits from a combined strategy with other drugs to maximize therapeutic effect while minimizing drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…A similar finding was reported by Wu et al [ 28 ], who determined the MIC 90 for tigecycline to be 1 μg/mL for S. maltophilia . Yue et al [ 29 ] demonstrated that a combination of tigecycline and azithromycin can successfully inhibit the formation of an S. maltophilia biofilm. Given the results of our study, tigecycline may be another effective treatment option for S. maltophilia infections.…”
Section: Discussionmentioning
confidence: 99%